2014
DOI: 10.1111/jan.12394
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of family and marital functioning at early postpartum

Abstract: Couple-based interventions should be initiated early during pregnancy by strengthening family sense of coherence and social support to promote positive family functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
(53 reference statements)
3
25
0
Order By: Relevance
“…Evidence of high participation rates is evident in other studies conducted in this region (e.g. Hmwe et al ; Ngai & Ngu ). Third, the high participation rate could also be due to the fact that limited tailored support is provided to Thai family caregivers in this situation (World Health Organization and Ministry of Public Health ); therefore, participants might have perceived the study could be beneficial to their situation.…”
Section: Discussionsupporting
confidence: 61%
“…Evidence of high participation rates is evident in other studies conducted in this region (e.g. Hmwe et al ; Ngai & Ngu ). Third, the high participation rate could also be due to the fact that limited tailored support is provided to Thai family caregivers in this situation (World Health Organization and Ministry of Public Health ); therefore, participants might have perceived the study could be beneficial to their situation.…”
Section: Discussionsupporting
confidence: 61%
“…Many studies sought to identify the relationship between socio-demographic factors and postpartum depression. A study by Fei-Wan Ngai demonstrated that women in steady relationships have a high level of family-related sense of coherence, which helps them adapt to new life situations [ 25 ]. In turn, Charline El-Hachem did not observe any significant impact of relationship status on the prevalence of postpartum depression among single women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, there was a notable association between postpartum mood disorders and the women's marital status. A study by Fei-Wan Ngai demonstrated that women in steady relationships have a high level of family-related sense of coherence, which helps them adapt to new life situations [22]. In turn, Charline El-Hachem did not observe any signi cant impact of relationship status on the prevalence of postpartum depression among single women [23].…”
Section: Discussionmentioning
confidence: 95%